Low ivermectin use among 5- to 6-year-old children: observations from door-to-door surveys in onchocerciasis-endemic regions in Africa. Issue 1 (28th June 2019) - Siewe Fodjo, J N; Mubiru, F; Ukaga, C; Logora, M Y; Mmbando, B P; Mandro, M; Njamnshi, A K; Colebunders, R
Abstract: During door-to-door surveys in onchocerciasis-endemic regions in Africa, the age-specific ivermectin coverage in 29 722 individuals was assessed. Children 5–6 y of age had significantly lower coverage compared with older participants. Insufficient ivermectin intake among young children could prolong onchocerciasis elimination prospects, as they may serve as human reservoirs of Onchocerca volvulus ; moreover, it increases the risk of developing onchocerciasis-associated epilepsy (OAE). The causes of the low ivermectin coverage observed among children 5–6 y of age need to be explored. Integrating ivermectin distribution into chemoprophylaxis strategies for other neglected diseases could increase coverage in a cost-effective manner.